Space use and its effects on reproductive success of anadromous Atlantic salmon - Tentelier, Cédric; Larranaga, Nicolas; Lepais, Olivier; Manicki, Aurélie; Rives, Jacques; Lange, Frédéric (Canadian journal of fisheries and aquatic sciences, 2016)
We combined habitat mapping, radio tracking of adults, redd mapping, and genetic parentage analysis on juveniles for 2 consecutive years to test eight predictions on the reproductive payoffs and individual features associated with space use tactics of anadromous Atlantic salmon (Salmo salar) in a natural population. Regarding payoffs, we found that (1) males settled in better habitat, visited more redds, and tended to get more mates than males settled in poorer habitat; (2) they also sired more offspring; (3) the latter effect was stronger in the first year, when redds were more aggregated; and (4) female reproductive success increased with habitat quality in their home range, especially in the first year. For individual features, (5) individuals that settled earlier in their home range had better habitat for juvenile production, but only in the first year; (6) females were less mobile than males, especially in the second year; (7) larger males did not settle in better habitats than smaller males; and (8) smaller males were not more mobile than larger males.